Measurement of deeply virtual Compton scattering at HERA - Chekanov, S; Derrick, M; Krakauer, D; Loizides, J; Magill, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Basile, M; et al. (2003)
The cross-section for deeply virtual Compton scattering in the reaction ep → eγp has been measured with the ZEUS detector at HERA using integrated luminosities of 95.0 pb-1 of e+p and 16.7 pb-1 of e-p collisions. Differential cross-sections are presented as a function of the exchanged-photon virtuality, Q2, and the centre-of-mass energy, W, of the γ*p system in the region 5 < Q2 < 100 GeV2 and 40 < W < 140 GeV. The measured cross-sections rise steeply with increasing W. The measurements are compared to QCD-based calculations. © 2003 Elsevier B.V. All rights reserved.